2016
DOI: 10.3168/jds.2015-9466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maturity and hybrid on ruminal and intestinal digestion of corn silage in dry cows

Abstract: The aim of this study was to evaluate the effect of stage of maturity at harvest on extent of starch, neutral detergent fiber (NDF), and protein digestion, and rumen fermentation in dry cows fed whole-plant corn silage from different hybrids. Four nonlactating Holstein cows cannulated at the rumen and proximal duodenum were fed 4 corn silages differing in hybrid (flint vs. flint-dent) and maturity stage (early vs. late) in a 4 × 4 Latin square design. From early to late maturity, starch content increased (from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
(78 reference statements)
2
17
0
2
Order By: Relevance
“…The forage DM yields measured here were high compared to other studies on triticale–legume intercrops (Arrigo, , Arrigo et al., ; Jacobs & Ward, ; Lithourgidis et al., ). The values recorded at late stage were in the range of the maize silages grown in the same experimental site (Peyrat, Baumont, Le Morvan, & Noziere, ).…”
Section: Discussionsupporting
confidence: 92%
“…The forage DM yields measured here were high compared to other studies on triticale–legume intercrops (Arrigo, , Arrigo et al., ; Jacobs & Ward, ; Lithourgidis et al., ). The values recorded at late stage were in the range of the maize silages grown in the same experimental site (Peyrat, Baumont, Le Morvan, & Noziere, ).…”
Section: Discussionsupporting
confidence: 92%
“…Those parameters averaged 6.9 ± 0.01 for pH, 13.3 ± 1.2 mg/dl for NH 3 -N, 57.5 ± 6.3 mmol/l for total VFA, whereas molar proportions (mol/100 ml) for VFA were as follows: 63.8 ± 0.1 for acetate, 22.7 ± 0.2 for propionate, 11.2 ± 0.1 for butyrate and 2.4 ± 0.1 for valerate. The effect of the diet on the fermentation pattern is well known and the values obtained in the present study are similar to those reported for non-lactating cows fed corn-silage-based diets (Peyrat et al, 2016) and a diet with a 50 : 50 forage : concentrate ratio based on corn silage, alfalfa hay and soybean meal (Shahmoradi et al, 2016).…”
Section: Resultssupporting
confidence: 89%
“…Vials containing only inoculum were used for blank correction. Once filled, the vials were sealed with rubber stoppers and aluminum caps, shaken and placed in an incubator (Shel Lab, Sheldon Manufacturing, Inc., Cornelius, OR, USA) at 39 ± 0.5 • C. The gas pressure in the headspace was measured manually by inserting a sterile needle connected to the pressure transducer at 3,6,9,12,15,18,21,24,30,36,48,60,72,96, and 144 h after inoculation. The volume of gas produced was estimated from the pressure values as proposed by López et al [13].…”
Section: Fermentation Kineticsmentioning
confidence: 99%